Efficacy of the FEV1/FEV6 ratio compared to the FEV1/FVC ratio for the diagnosis of airway obstruction in subjects aged 40 years or over - Rosa,F.W. (2007)
The present cross-sectional, population-based study was designed to evaluate the performance of the FEV1/FEV6 ratio for the detection of airway-obstructed subjects compared to the FEV1/FVC <0.70 fixed ratio test, as well as the lower limit of normality (LLN) for 1000 subjects ³40 years of age in the metropolitan area of São Paulo, SP, Brazil. After the exclusion of 37 (3.7%) spirometries, a total of 963 pre-bronchodilator (BD) and 918 post-BD curves were constructed. The majority of the post-BD curves (93.1%) were of very good quality and achieved grade A (762 curves) or B (93 curves). The FEV1/FEV6 and FEV1/FVC ratios were highly correlated (r² = 0.92, P < 0.000). Two receiver operator characteristic curves were constructed in order to express the imbalance between the sensitivity and specificity of the FEV1/FEV6 ratio compared to two FEV1/FVC cut-off points for airway obstruction: equal to 70 (area under the curve = 0.98, P < 0.0001) and the LLN (area under the curve = 0.97, P < 0.0001), in the post-BD curves. According to an FEV1/FVC <0.70, the cut-off point for the FEV1/FEV6 ratio with the highest sum for sensitivity and specificity was 0.75. The FEV1/FEV6 ratio can be considered to be a good alternative to the FEV1/FVC ratio for the diagnosis of airway obstruction, both using a fixed cut-off point or below the LLN as reference. The FEV1/FEV6 ratio has the additional advantage of being an easier maneuver for the subjects and for the lung function technicians, providing a higher reproducibility than traditional spirometry maneuvers.